Limits of using oligonucleotides for allele-selective inhibition at trinucleotide repeat sequences – targeting the CAG repeat within ataxin-1. (20th February 2020) - Hu, Jiaxin; Corey, David R.
Abstract: Trinucleotide repeats are responsible for many genetic diseases. Previous studies have shown that duplex RNAs (dsRNAs) can be used to target expression of a mutant repeat allele while leaving expression of the wild-type allele untouched, creating opportunities for allele-selective inhibition and better therapeutic outcomes. In contrast to successes with other genes, we report here that we cannot achieve allele-selective inhibition when targeting the expanded CAG repeat within Ataxin-1 (ATXN1), the cause of spinal cerebellar ataxia-1 (SCA1). The most likely explanation for this unfavorable outcome is that the mean CAG repeat number within wild-type ATXN1 is relatively high compared to other trinucleotide repeat diseases. Because the wild-type repeat number is high, it is likely that there is poor discrimination between the mutant and wild-type repeat and less opportunity for allele-selective inhibition across the entire spectrum of mutations found in SCA1 patients. Our data support the conclusion that the potential for multiple cooperative binding interactions is a critical factor governing allele-selective recognition of trinucleotide repeat genes by duplex RNAs. These results should be helpful in predicting which diseases and which patients are most likely to benefit from allele-selective targeting of expanded repeats.